PROBLEMS FOR DEVELOPMENT OF TECHNIQUE AND TECHNOLOGY OF COMPOSITE INSULATORS IN WESTERN EUROPE - L. Suboch (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2005)
Problems concerning development of composite insulators and insulator types for electric mains with a voltage higher than 1000 kV in the Western Europe are considered in the paper. It shows the prospects for obtaining a number of polymer materials (epoxy resin, silicone elastomer, ethylene-propylene rubber, polytetraftuoroethylene etc.), reinforcing materials and ageing problem of polymer insulation.